Energy metabolic shift contributes to the phenotype modulation of maturation stage ameloblasts - Arai, Haruno; Inaba, Akira; Ikezaki, Shojiro; Kumakami-Sakano, Mika; Azumane, Marii; Ohshima, Hayato; Morikawa, Kazumasa; Harada, Hidemitsu; Otsu, Keishi (Frontiers in Physiology, 2022)
Maturation stage ameloblasts (M-ABs) are responsible for terminal enamel mineralization in teeth and undergo characteristic cyclic changes in both morphology and function between ruffle-ended ameloblasts (RA) and smooth-ended ameloblasts (SA). Energy metabolism has recently emerged as a potential regulator of cell differentiation and fate decisions; however, its implication in M-ABs remains unclear. To elucidate the relationship between M-ABs and energy metabolism, we examined the expression pattern of energy metabolic enzymes in M-ABs of mouse incisors. Further, using the HAT7 cell line with M-AB characteristics, we designed experiments to induce an energy metabolic shift by changes in oxygen concentration. We revealed that RA preferentially utilizes oxidative phosphorylation, whereas SA depends on glycolysis-dominant energy metabolism in mouse incisors. In HAT7 cells, hypoxia induced an energy metabolic shift toward a more glycolytic-dominant state, and the energy metabolic shift reduced alkaline phosphatase (ALP) activity and calcium transport and deposition with a change in calcium-related gene expression, implying a phenotype shift from RA to SA. Taken together, these results indicate that the energy metabolic state is an important determinant of the RA/SA phenotype in M-ABs. This study sheds light on the biological significance of energy metabolism in governing M-ABs, providing a novel molecular basis for understanding enamel mineralization and elucidating the pathogenesis of enamel hypomineralization.